2009
DOI: 10.1002/art.24718
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of cathepsin K in synovium leads to progression of osteoarthritis in rabbits

Abstract: Objective. The hypothesis of this study was that synovial factors playing a pivotal role in the pathogenesis of osteoarthritis (OA) and thus gene expression in the synovium would be altered at the initial stage of OA. The aims of this study were to identify the candidate genes in synovium related to OA initiation, to evaluate cartilage degeneration after knockdown of the gene using small interfering RNA (siRNA) gene silencing in the knee joints at the initial stage of OA, and to determine the potential role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…The mRNA levels for cathepsin K showed significant upregulation in the first week, reached peak levels at 2 weeks and then returned to near-normal levels by 4 weeks. Interestingly, following ACL transection in a rabbit model of OA development, cathepsin K gene expression levels were shown to be significantly increased by 7 days after surgery [45]. Thus, the expression of cathepsin K followed patterns similar to those observed for MMPs and the pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The mRNA levels for cathepsin K showed significant upregulation in the first week, reached peak levels at 2 weeks and then returned to near-normal levels by 4 weeks. Interestingly, following ACL transection in a rabbit model of OA development, cathepsin K gene expression levels were shown to be significantly increased by 7 days after surgery [45]. Thus, the expression of cathepsin K followed patterns similar to those observed for MMPs and the pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 65%
“…Some studies suggest that downregulation of this protease may lead to a delay in the OA development, as it suppresses both inflammation and osteoclastic bone resorption [46]. However, studies using small interfering RNAs have demonstrated that in the initial development of OA, suppression of cathepsin K leads to increased expression of MMP-13 which in turn leads to cartilage degeneration, which is the hallmark of OA progression [45].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies were gene therapy studies, such as siRNA or protein delivery into chondrogenic cell lines, or, animal models of arthritis [11][12][13] . In other systems, such as chicken or mouse, electroporation of facial mesenchyme has been challenging (personal communications, Dept of Craniofacial Development, KCL).…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin K gene and protein expression is upregulated in the synovium in a rabbit model of anterior cruciate ligament transection-induced OA. Downregulation of cathepsin K by an electroporation-assisted siRNA transduction in the synovium leads to OA progression in rabbits, indicating that cathepsin K is involved in cartilage degeneration [61]. So far, siRNA therapy of OA (e.g., ad-siRNA (NF-kB p65) or electrotransfer of siRNA against cathepsin K) is in various preclinical development stages [60,61] and no clinical trials have been reported.…”
Section: Oamentioning
confidence: 99%